Split Tensile Strength of Self Compacting Concrete with Artificial Lightweight Aggregate - Dhiafah Hera Darayani (Litbang Pemas - Universitas Islam Lamongan, 2022)
Earthquake damage to buildings is directly proportionate to the weight of the structure. Selfcompacting concrete is a type of concrete that can consolidate without the use of vibrator. To minimize damage structures caused by earthquakes, infrastructure development needs lighter materials and superior workmanship. Lightweight aggregate can reduce weight of the structure, SCC with ALWA is a solution to reduce dead load of the structure with ease of execution. The purpose of this study is to see how much the split tensile strength influences the composition of ALWA as coarse aggregate substitute in Normal Concrete and SCC. The proportions of ALWA that substituted into concrete were 0%, 15%, 50% and 100%. There are 24 cylindrical specimens, each measuring 100 mm in diameter and 200 mm in height. The analysis was carried out using ASTM C 496/C 496M. The results of split tensile strength show that the higher variation in the composition of ALWA, the lower split tensile strength produced. The addition of ALWA as a substitute for coarse aggregate in a mixture of normal and SCC concrete was most effective at 15% ALWA with a split tensile strength of normal concrete 2.23 MPa and SCC 2.32 MPa.